Decision-making skills and leadership effectiveness among public school administrators in Tarragona District, Davao Oriental - Naomi C. Quinal; Helina Jean P. Dupa (Davao Research Journal)
This study determined the influence of decision-making skills on leadership effectiveness among public school administrators in Tarragona District, Davao Oriental division. It employed a descriptive-correlational research method. Gathering data from 143 respondents, results revealed that female school administrators had (n=72) higher educational qualifications compared to their male counterparts (n=71). Most of the administrators were in their retirement age (x=54-60). They had moderate levels of decision-making skills, specifically in rational, intuition, dependent, avoidant, and spontaneous decision-making. In terms of leadership effectiveness, the school administrators were categorized as high in instructional programs, financial resource management, and school community relations while moderate level in staff administration and student services. There was a strong positive correlation between decision-making skills and the leadership effectiveness of the administrators in terms of their educational attainment. The direct effect of decision-making skills and the leadership effectiveness of public school administrators was categorically small in size. Among the fit indices for decision-making and leadership inventory skills, only Joreskog-Sorbom's Fit Index (GFI) was the only best-fit model. Parallel studies may be conducted by examining other aspects and the nature of variables related to decision-making skills and leadership effectiveness so that further assessments on the reliability and validity of the data in this research could be ascertained.